2021
DOI: 10.1186/s42774-021-00061-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stall control over a rotor airfoil based on AC DBD plasma actuation

Abstract: At present, the control capability of dielectric barrier discharge (DBD) plasma actuation covers the flow velocity range of helicopter’s retreating blades, so it is necessary to extend it to the dynamic stall control of rotor airfoils. A DBD plasma actuator was adopted to control the dynamic stall of an oscillating CRA309 airfoil in this paper. The effectiveness of alternating current (AC) DBD plasma actuation on reducing the area of lift hysteresis loop of the oscillating airfoil was verified through pressure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…When the pulsemodulated voltage was applied to the DBD actuator, the actuation is cycled on and off with an unsteady period, thus, unsteady plasma actuation is generated with a series of unsteady vortices moving along the wall surface. When DC=100%, the actuator is driven by continuous AC voltages and steady plasma actuation can be generated with a tangential jet along the wall [14].…”
Section: Methodsmentioning
confidence: 99%
“…When the pulsemodulated voltage was applied to the DBD actuator, the actuation is cycled on and off with an unsteady period, thus, unsteady plasma actuation is generated with a series of unsteady vortices moving along the wall surface. When DC=100%, the actuator is driven by continuous AC voltages and steady plasma actuation can be generated with a tangential jet along the wall [14].…”
Section: Methodsmentioning
confidence: 99%
“…The unsteady AC DBD plasma actuator on the other hand could reduce the area of hysteresis loop by 30% at Re = 5.0 × 10 5 , for CRA309 airfoil. 31…”
Section: Introductionmentioning
confidence: 99%
“…The control of dynamics stall can be achieved through active flow control mechanism such as dielectric barrier discharge (DBD) plasma actuators. 21,[31][32][33] Singhal et al reported that an increase in the frequency of plasma actuation reduces the oscillatory behavior in the lift curve of NACA 0015 and the oscillations are completely wiped out for actuation Strouhal number of 2 and more. 33 These high frequency plasma actuations also reduce the area of hysteresis loop and the strength of DSV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation